Answer:
3 and 28
Step-by-step explanation:
note (
)(x ) = ![\frac{f(x)}{g(x)}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%29%7D%7Bg%28x%29%7D)
![\frac{f(x)}{g(x)}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%29%7D%7Bg%28x%29%7D)
=
and
(
)(4) =
=
=
= 3
-------------------------------------------------------
(f + g)(x) = f(x) + g(x)
f(x) + g(x)
= x² + 2x - 3 + x² - 9 = 2x² + 2x - 12 and
(f + g)(4) = 2(4)² + 2(4) - 12 = 2(16) + 8 - 12 = 32 + 8 - 12 = 28
Answer:
the answer is .6
Step-by-step explanation:
so 30 minus 24 is 6 turn 6 into percentage which is 0.6
Answer:
c = a - 16
Step-by-step explanation:
Given
a = b + 12 ( subtract 12 from both sides )
a - 12 = b
Substitute b = a - 12 into b = c + 4
a - 12 = c + 4 ( add 12 to both sides )
a = c + 16 ( subtract 16 from both sides )
c = a - 16
Answer:
idk bro but ily
Step-by-step explanation:
Answer:
y=2/1x
Step-by-step explanation:
Subtract (6,8) by (1, -2)
8--2/6-1=10/5
Simply
10/5=2
Plug in
y=2x